1993
DOI: 10.1136/jcp.46.12.1137
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human herpes virus-6 genomes in lymphoid malignancy in Japan.

Abstract: Ninety cases of malignant lymphoma and 56 cases of reactive lymphadenopathy were studied using Southern blot analysis and the polymerase chain reaction to identify human herpes virus-6 (HHV-6) DNA. This was detected in cases of lymphoid malignancy at a rate which ranged from 50.0% to 68.8%. There were no differences in rates for different types of lymphoid malignancies. Herpes virus-6 DNA was detected by PCR in lymphoid malignancies less frequently than in reactive lymphadenopathies. It was not detected in lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
2
15
1
Order By: Relevance
“…The HHV-6 U22 gene was detected in 68 of the 86 patients (79.1%). Similar prevalences were found by others [Sumiyoshi et al, 1993;Krueger et al, 1994;Valente et al, 1996]. In contrast to EBV positive patients, the patients suffering from the nodular sclerosis type of Hodgkin's lymphoma were positive most frequently for HHV-6 (83.6%).…”
Section: Discussionsupporting
confidence: 89%
“…The HHV-6 U22 gene was detected in 68 of the 86 patients (79.1%). Similar prevalences were found by others [Sumiyoshi et al, 1993;Krueger et al, 1994;Valente et al, 1996]. In contrast to EBV positive patients, the patients suffering from the nodular sclerosis type of Hodgkin's lymphoma were positive most frequently for HHV-6 (83.6%).…”
Section: Discussionsupporting
confidence: 89%
“…Our present large-scale study, using sensitive PCR analysis of 100 ng of lymph node tissue DNA, detected the HHV-6 genome in 35.1% of all HD patients. Minor differences between our results and those reported by others (10,40,43) probably reflect variations in the sensitivities of the various tests employed and in the amounts of DNA analyzed, as well as differences in the populations studied. By contrast, however, Shiramizu et al (39) found no HHV-6 sequences in a cohort of 47 pediatric HD patients.…”
Section: Discussioncontrasting
confidence: 55%
“…Since then, many studies aimed at identifying the HHV-6 genome in pathologic specimens using polymerase chain reaction (PCR) have been reported (Table 1). [28][29][30][31][32][33][34][35][36] Frequencies of positive HHV-6 DNA appear to vary widely among these studies, and may depend on the differences in PCR sensitivity for each study. Variant B has been identified more frequently than variant A.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%